2011
DOI: 10.1371/journal.pone.0019097
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cardiovascular Fibrosis Using Novel Fluorescent Probes

Abstract: Cardiovascular fibrosis resulted from pressure overload or ischemia could alter myocardial stiffness and lead to ventricular dysfunction. Fluorescently labeled collagen-binding protein CNA 35, derived from the surface component of Staphylococcus aureus, and a novel synthetic biphenylalanine containing peptide are applied to stain fibrosis associated collagen and myocytes, respectively. Detailed pathological characteristics of cardiovascular fibrosis could be identified clearly in 2 hours. This staining pair re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 19 publications
(26 reference statements)
1
30
0
Order By: Relevance
“…Thus Cna can only bind to collagen triple helix monomers but not to collagen fibers or fibrils. This property has recently been taken advantage of when investigators have used a fluorescently tagged form of Cna to detect monomeric collagen product during fibrosis (45). This specificity also limits the type of collagenous tissue that can be targeted in Cna-dependent adhesion because collagen is primarily found in higher orders of fibrous super structures in healthy mature tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Thus Cna can only bind to collagen triple helix monomers but not to collagen fibers or fibrils. This property has recently been taken advantage of when investigators have used a fluorescently tagged form of Cna to detect monomeric collagen product during fibrosis (45). This specificity also limits the type of collagenous tissue that can be targeted in Cna-dependent adhesion because collagen is primarily found in higher orders of fibrous super structures in healthy mature tissues.…”
Section: Discussionmentioning
confidence: 99%
“…34 Previous studies have used these methods to visualize collagen deposition and measure the size of the scar in diseased cardiac tissues. 3,5,35 We have shown that the scar size measured as percentage of tissue section showing collagen deposition from FT-IRIS analysis strongly correlated with the measurements achieved by trichrome staining of a section from same heart tissues. The fact that samples used in this analysis were comprised of two groups of animals, a treatment group with targeted delivery of VEGF to infarcted myocardium and a control untreated group, demonstrates the applicability of the methodology for different treatment conditions.…”
Section: Discussionmentioning
confidence: 52%
“…The samples were embedded in optimum cutting temperature and stored at Ϫ80°C. Masson's Trichrome was performed as previous described (10). Paraffined samples were used for immunohistochemistry of CD31 (ABCAM, ab28364, dilution 1:100).…”
Section: Methodsmentioning
confidence: 99%